IMPLEMENTATION OF THE AVAILABILITY OF BREASTFEEDING ROOMS IN PUBLIC FACILITIES IN BEKASI CITY - Supriyanto, Yanto; Dian Rahayu, Susi; Agustin, Dwi (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2024)
The United Nations Children's Fund (UNICEF) mentions that exclusive breastfeeding is one of the efforts to prevent infant and toddler deaths in the world. In fact, in Indonesia, the exclusive breastfeeding program is one of the government-supported programs. This can be seen from several regulations that the Government has issued to support the exclusive breastfeeding program, including Law Number 36 of 2009 concerning Health, and Government Regulation Number 33 of 2012 concerning Exclusive Breastfeeding. One of the efforts to support the exclusive breastfeeding program is to provide support in the form of the availability of breastfeeding rooms in the workplace and public facilities, as stated in the Regulation of the Minister of Health of the Republic of Indonesia Number 15 of 2013 concerning Procedures for Providing Special Facilities for Breastfeeding and or Expressing Breast Milk. Support for the provision of breastfeeding rooms is not only carried out by the central government but also by local governments, one of which is Bekasi City, through Bekasi Mayor Regulation Number 55 of 2017 concerning the Provision of Breastfeeding Rooms in Government/Private Workplaces and Other Public Facilities. However, not all public facilities in Bekasi City have been equipped with breastfeeding room facilities. This research will examine the availability of breastfeeding rooms in Bekasi City, with the research locus at three stations in Bekasi City, namely Kranji Station, Bekasi Station, and East Bekasi Station. This research uses a qualitative research method with a case study approach. The data acquisition mechanism in this study uses observation and in depth interview methods, involving various relevant stakeholders such as the Head of the Station, the Health Office, and the community of Railway station users in Bekasi City.